2006
DOI: 10.1093/jac/dkl380
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular accumulation of linezolid in Escherichia coli, Citrobacter freundii and Enterobacter aerogenes: role of enhanced efflux pump activity and inactivation

Abstract: The intracellular concentration of linezolid is comparatively low owing to efficient efflux of the drug and could be increased substantially by inhibition of RND-type efflux pumps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 18 publications
1
68
0
1
Order By: Relevance
“…In this regard, it has been demonstrated that the intracellular concentration of linezolid in strains of E. coli, E. aerogenes, and Citrobacter freundii is comparatively low due to the efficient efflux of the drug by the resistance-nodulationdivision-type efflux pump (25).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it has been demonstrated that the intracellular concentration of linezolid in strains of E. coli, E. aerogenes, and Citrobacter freundii is comparatively low due to the efficient efflux of the drug by the resistance-nodulationdivision-type efflux pump (25).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro selection of fluoroquinolone-resistant mutants showed the importance of increased efflux in practically all cases (241). Intrinsic resistance to linezolid is mediated by AcrB in this species as well as others (242). A C. freundii isolate containing the plasmid-encoded RND pump was reported recently (243) (see Drug Efflux Genes on Plasmids, below).…”
Section: Citrobacter Sppmentioning
confidence: 88%
“…Newer ketolides (e.g., cethromycin and solithromycin) and oxazolidinones (posizolid, radezolid, and tedizolid) are still the agents mainly against Gram-positive bacteria (944), and the lack of potency for Gram-negative bacilli is likely attributable to drug efflux and the OM permeability barrier, as shown with earlier members of their classes (85,242,266,971). For example, solithromycin is clearly a strong substrate for three pumps, MtrCDE, MacAB, and NorM, of different transporter families (647).…”
Section: Multidrug Efflux Pumps As a Challenge In Drug Developmentmentioning
confidence: 99%
“…Linezolid appeared on the market in 2000 for treatment of serious infections caused by Gram-positive bacteria resistant to other antibiotics, including streptococci, vancomycin-resistant enterococci (VRE), and methicillin-resistant Staphylococcus aureus (MRSA) (9). It is not well suited for fighting Gram-negative pathogenic bacteria that are intrinsically resistant due to efflux pumps that force linezolid out of the cell faster than it can accumulate (1,74). Linezolid is one of the few truly new antibiotics that have been introduced in many years, as most newcomers are derivatives of existing drugs.…”
Section: Linezolidmentioning
confidence: 99%